Microwave wireless power transmission technology index system and test evaluation methods - Changfu Wang; Wanli Xu; Chunlin Zhang; Mengyi Wang; Xudong Wang (EURASIP Journal on Advances in Signal Processing, 2022)
Abstract Microwave wireless power transmission technology has broad application prospects in improving the endurance and range of unmanned equipment. It is also of great significance in the field of the Internet of things, which can effectively solve the problem of energy supply for devices in the Internet of things. In addition, using vehicle-mounted microwave wireless power transmission to power multi-objective unmanned aerial vehicle swarms and to build an air-ground integrated power transmission network. In this study, the corresponding technical index system and test evaluation methods, which are conducive to promoting the development and progress of this technology, were established. The topology of a microwave wireless power transmission system was analyzed, and technical evaluation indices were developed for microwave wireless power transmission systems, signal generators, power amplifiers, transceiver antennas, and rectifier circuits. Test evaluation methods were established consisting of test equipment, methods, and processes to provide powerful technical means for the development of microwave wireless power transmission systems.